Eco fashion: uma perspectiva dos consumidores sobre a moda sustentável - Aragão, Daniela da Silva (Brasil, 2025)
The study analyzed consumers' perspectives on sustainable fashion, investigating attitudes, perceptions, and behaviors toward eco-friendly products, as well as the factors and barriers influencing their purchasing decisions. Using a quantitative and descriptive approach, online questionnaires were administered to clothing consumers over the age of 18, covering topics ranging from respondent profiles to their attitudes and consumption influences. The results show that although consumers value sustainability and express interest in sustainable fashion, they face barriers such as high costs and convenience, which limit effective adoption. It is concluded that while awareness is increasing, there is a gap between intention and behavior, indicating the need for strategies to make sustainable products more accessible and informative.